Effects of Pesticides on Cyanobacterial Growth and Biochemical Parameters: Impacts of Pesticides on Cyanobacterial Growth and Metabolic Function (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Pesticides are chemicals that are used to keep pests out of a building. Herbicides, insecticides,and a variety of other compounds are included in the phrase pesticide (which may include insect growthregulators, termiticides, etc.) Cyanobacteria are among the oldest living forms on the earth, stretchingback billions of years. They are necessary for photosynthesis and the global carbon and nitrogen cycles.There are cyanobacterial species with a wide range of physical properties that may live in a given habitathappily and mutually beneficially.